Passive Filter Design To Reduce Electrical Disturbances In The Manufacturing Industry - Solihin, Muhammad Dani; Astrid, Erita; Harahap, Muchsin; Affandi, Marwan; Isnaini, Muhammad (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
Industry is one of the economic sectors that plays a role in processing environmental resources into products with higher utility values. This process includes design activities, industrial engineering, and service provision. Matra Abadi Workshop, a manufacturing industry that in its operations produces harmonic currents in the electric power system network, especially in low-order harmonics such as 3rd, 5th, 7th, 9th, and 11th. To reduce the negative impact of harmonics on the power system, the use of passive harmonic filters is required. Among the types of filters used, single tuned filters are a common choice because of their simple construction and effectiveness in reducing certain order harmonics that exceed the IEEE 512–2014 standard limits. This study discusses the implementation of both types of filters in a manufacturing industry environment. The harmonic reduction process is carried out through filter design and testing using Matlab/Simulink software-based simulations. The simulation results show that after the application of passive filters, the harmonic current levels in all load configurations were successfully suppressed to within the IEEE 512–2014 standard limits. The reduction in Total Harmonic Distortion (THDi) after the application of the single tuned filter was recorded in the range of 17.86% to 11.06%. In addition, there was an increase in the power factor from 0.68 before the filter was installed to 0.91 after the installation, which indicates an improvement in the overall power system performance.